Coccolith species abundances in ODP Hole 162-984C from the subpolar North Atlantic Ocean for the past 24 ka - Karl-Heinz Baumann (PANGAEA, 2024)
Coccolithophore assemblage data from sediment core 162-984C from the subpolar North Atlantic ocean spanning the past 24 ka. The assemblage data were used to assess changes in biodiversity and assemblage composition during the past 24 ka, i.e., from the Last Glacial Maximum (LGM) to the current warm period covering the last deglaciation. Samples were analysed at 2-32 cm intervals and were prepared using a combined dilution/filtering technique as described by Andruleit (1996, doi:10.2307/1485964). Between 50 and 150 mg of dry bulk sediment was brought into suspension using demineralized water buffered with ammonia (pH ~ 8.5-9). The suspension was ultrasonicated for 15 to 30 s, split (split factor = 100) using a rotary splitter and filtered onto polycarbonate membrane filters (0.4 μm pore size) using a vacuum pump. Samples were dried at 40°C for 24 h before ~1x1 cm filter aliquots were mounted on an aluminium stub that was prepared with electroconductive, self-adhesive, carbon-based discs (PLANO Leit tabs). The mounted samples were sputtered with gold/palladium in a Polaron SC7640 Sputter Coater. Coccolith counts (N) were made manually using a Zeiss DSM 940A scanning electron microscope at 3,000x and 5,000x magnification. Where possible, a minimum of 300 coccoliths were counted. In some samples fewer coccoliths were counted due to very low abundances in the LGM. Sample mass (m), magnification, split factor (k) and the area of the scanned transect (A) and the filter (F) are given for all samples to allow calculation of the concentration of coccoliths per gram of dry bulk sediment, which was calculated using: (F*N)/(k*A*m). Coccolithophore taxonomy follows Young et al. (2003, doi:10.58998/jnr2297). Species not reported in the data are assumed to be absent (that is, zero abundance). Two subspecies of Calcidiscus leptoporus were distinguished: Calcidiscus leptoporus subsp. quadriperforatus and Calcidiscus leptoporus subsp. leptoporus. The ladder was further subdivided into small (< 5 μm) and larger (>= 5 μm) specimens. Furthermore, two subspecies of Coccolithus pelagicus were distinguished: Coccolithus pelagicus subsp. braarudii and Coccolithus pelagicus subsp. pelagicus. Counts of unidentified specimens are given. The chronology of the time series presented here is the revised age model included in the PALMOD 130k marine palaeoclimate data synthesis V1.1 (Jonkers et al., 2020, doi:10.5194/essd-12-1053-2020). It is based on radiocarbon ages measured on the planktonic foraminifera G. bulloides and N. pachyderma as well as tephra layers and benthic foraminifera δ18O isotope data calibrated to regional benthic foraminifera δ18O stacks (Lisiecki and Stern, 2016, doi:10.1002/2016pa003002).
In: Baumann, K-H (2024): Coccolith species abundances in sediment cores 162-984C, 162-980, GeoB11035-1, GeoB5546-2, M35003-4 and GeoB3104-1 from the North Atlantic Ocean for the past 24 ka [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.965722